Mechanical Energy Dissipation Through the Ossicular Chain and Inner Ear Using Laser Doppler Vibrometer Measurement of Round Window Velocity. Issue 3 (March 2020) - Ryan, Matthew; Lally, John; Adams, Jason K.; Higgins, Sophie; Ahmed, Mostafa; Aden, James; Esquivel, Carlos; Spear, Samuel A.
Abstract : Hypothesis: Round window velocity measurements should correlate closely with vibration measurements taken at proximal points along an intact chain over a set frequency range. These round window vibration measurements should be similar to the vibration measurements taken of the ossicles if mechanical energy is conserved through the vestibular organ. Background: To date there has not been a study which compares vibratory velocity measurements through an intact ossicular chain to the level of the round window. This study attempted to quantify the degree of mechanical energy transmission and suspected dissipation through the ossicular chain and vestibular organ through incus, stapes, and round window velocity measurements in response to sound stimulus. Methods: Five thawed human temporal bones with intact ossicular chain and tympanic membrane underwent complete mastoidectomy and a facial recess approach. A laser Doppler vibrometer (LDV) was mounted on the operating microscope to measure vibration of incus, stapes, and round window in response to a sound stimulus within the external auditory canal. Sound stimulus frequencies ranged from 0.5 to 4 kHz at 90 dB SPL. Results: Vibration velocity was measured across the frequency range for each incus, stapes, and round window. Vibration velocity curves obtained over the frequency range were similar for each of the bones with a notable resonant frequency around 2 kHz. The incus and stapes curve amplitudes were nearly identical with similar maximum velocity and frequency at which this maximal velocity was noted. Round window vibration velocity demonstrated a unique peak velocity. Transfer function measurements of the stapes and round window demonstrated markedly similar curves. The variation in velocity between temporal bones in response to the standardized stimulus was more dramatic in the round window measurements when compared with the incus and stapes. Conclusions: This study supports the concept that round window transfer function is equivalent to stapes footplate transfer function when subjected to the same acoustic stimuli. This study also demonstrates that the round window is a much more difficult target to measure when using LDV technology and improvements in experimental design are required to better understand round window physiology in relation to transfer of acoustic vibratory stimulus transferred throughout the middle ear. A complete and thorough understanding of the biophysical properties of the middle and inner ear are critical for optimal ossiculoplasty outcomes and the development of future ossicular prosthetics.